Individual Differences in Heparin Sensitivity and Their Effect on Heparin Anticoagulation During Arterial Vascular Surgery. (October 2017) - Veerhoek, D.; Groepenhoff, F.; van der Sluijs, M.G.J.M.; de Wever, J.W.B.; Blankensteijn, J.D.; Vonk, A.B.A.; Boer, C.; Vermeulen, C.F.W.
Abstract : Objectives: To investigate whether a fixed heparin dose results in adequate heparinisation levels and consequent inhibition of haemostatic activation in all patients. Methods: This prospective clinical pilot study included 24 patients undergoing arterial vascular surgery. Individual heparin responsiveness was assessed using the Heparin Dose Response (HDR) test, while the activated clotting time (ACT) and heparin concentration were measured to monitor the peri-procedural degree of anticoagulation. Finally, peri-operative haemostasis was evaluated with rotational thromboelastometry (ROTEM). Results: Eight patients were identified with reduced heparin sensitivity (RS group) and 16 patients with normal heparin sensitivity (NS group). Compared with the NS group, the RS group showed less prolonged ACTs after heparinisation with heparin concentrations below the calculated target heparin concentration. ROTEM revealed shorter clot formation times in the intrinsically activated coagulation test (INTEM) 3 min (114 ± 48 s vs. 210 ± 128 s) and 30 min after the initial heparin bolus (103 ± 48 s vs. 173 ± 81 s) in the RS group compared with the NS group. In the RS group, one patient developed a major thromboembolic complication. Conclusions: This study shows that a third of the study population had reduced heparin sensitivity, which was associated with lower levels of heparinisation, and lower inhibition levels of clot initiation and clot formation. Identifying patients with reduced heparin sensitivity by monitoring the anticoagulant effect of heparin could decrease the risk of thrombotic complications after arterial vascular surgery.